Introduction of Sharia Financial Literacy at Majlis Taklim Nurul Jamal Leles Garut - Susanti, Illa; Ulum, Miftahul (Fin Sinergy: Jurnal Manajemen Keuangan, 2023)
This research aims to explore the effectiveness of introducing sharia financial literacy at Majlis Taklim Nurul Jamal, Leles Garut. Given the importance of understanding Islamic finance in the context of Islamic economics, this research focuses on how knowledge and practice of Islamic finance can be improved among Majlis Taklim members. The methodology used includes surveys and in-depth interviews with Majlis members, teachers and local community leaders. Surveys were conducted to assess the level of Islamic financial literacy before and after educational sessions, while interviews were used to gain deeper insight into perceptions and attitudes towards Islamic finance. The research results show that there is a significant increase in understanding of sharia financial concepts, such as the principle of profit sharing, fairness in transactions, and avoidance of usury, after attending a series of educational sessions. Many respondents reported positive changes in attitudes towards Islamic financial products and services. In addition, this research also identified several challenges, including a lack of access to reliable sources of information and the need for educational materials that are more relevant to the local context. This research provides valuable insight into the importance of Islamic financial literacy in Muslim communities and offers recommendations for further development of literacy programs. The implications of these findings are important for policy developers, Islamic financial institutions, and educators in the field of Islamic economics, providing a basis for more effective intervention strategies in increasing Islamic financial literacy in local communities.